1971
DOI: 10.1111/j.1432-1033.1971.tb01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Immunochemical Studies of the Surface Antigens of Escherichia coli Strains O8:K87(B?):H19 and (O32):K87(B?):H45

Abstract: The O-antigenic lipopolysaccharides and the acidic polysaccharides isolated from Eschrichia coli strains 0 8 : K87(B 2) : H45 were compared with respect to chemical composition and serological specificity.The O-specific polysaccharide moiety of the lipopolysaccharide from E . coli 08 :K87(B ?) : Hi9 contains mannose as the sole sugar constituent, whereas the (032)-specific polysaccharide moiety of the lipopolysaccharide from E . coli (032) :K87(B 2 ) :H45 consists of glucose, galactose, glucuronic acid, N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…For G7 or Bi 316-42 we suggest that at some time in the past, the major O-antigen structures were O32 and O104, respectively, but during adaptation to a new niche, the O8 or the O9 antigen was acquired and became the major LPS polysaccharide, with the O32 or O104 antigen converted to a capsule, although with a proportion still present in LPS as K LPS . This hypothesis is supported by the fact that the structures of capsules K87 and K9 are identical to those of O32 and O104, respectively (12,20).…”
Section: Discussionsupporting
confidence: 66%
“…For G7 or Bi 316-42 we suggest that at some time in the past, the major O-antigen structures were O32 and O104, respectively, but during adaptation to a new niche, the O8 or the O9 antigen was acquired and became the major LPS polysaccharide, with the O32 or O104 antigen converted to a capsule, although with a proportion still present in LPS as K LPS . This hypothesis is supported by the fact that the structures of capsules K87 and K9 are identical to those of O32 and O104, respectively (12,20).…”
Section: Discussionsupporting
confidence: 66%
“…boydii type 6 [19] lipopolysaccharides indicated that the polysaccharide chain of certain Shigellu lipopolysaccharides from serogroups A, C and D could be the acidic ones. Till the recent time, the occurrence of acidic polysaccharide chains was ascertained only in lipopolysaccharides of some Escherichia coli strains [20]. The charged (capsular) polysaccharides are known to endow the bacteria with the resistance to host defence mechanisms [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In this context it is interesting to note that in E. coli strains 08 and 09 no rfc locus (determining the polymerase for lipidlinked oligosaccharides [see reference 279]) was found. MULTIPLE OCCURRENCE OF POLYSAC-CHARIDE ANTIGENS E. coli strain D227, 08:K87 was originally believed to contain a neutral cell wall LPS and, in addition, an acidic capsular polysaccharide (108,113,210,286). It was found later (Jann and Jann, manuscript in preparation) that the K87 antigen was actually an acidic LPS, so the strain contains two LPS in the outer membrane.…”
Section: Biosynthesis Of 0 and K Antigensmentioning
confidence: 99%